2014
DOI: 10.1186/1477-5956-12-33
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the leaf proteome during flooding stress and the induction of programmed cell death in maize

Abstract: BackgroundMaize is a major economic crop worldwide, with substantial crop loss attributed to flooding. During a stress response, programmed cell death (PCD) can be an effective way for plants better adapt. To identify flooding stress related PCD proteins in maize leaves, proteomic analysis was performed using two-dimensional fluorescence difference gel electrophoresis (2D-DIGE) and mass spectrometry.ResultsComparative proteomics was combined with physiological and biochemical analysis of maize leaves under flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 98 publications
(98 reference statements)
3
33
0
Order By: Relevance
“…In total, 34 target genes were identified, among which, S-adenosylmethionine synthetase (SAM) was the only predicted target of the only known differentially expressed miRNA mir-2788. SAM is also known as methionine adenosyltransferase (MAT), catalyzes the formation of S-adenosylmethionine by joining methionine and ATP (Horikawa et al 1990), and plays an important role in plant responses to salt, drought, alkali, and flood stresses (Kamal et al 2012;Chen et al 2014). SAM is also a methyl donor, which controls gene expression by DNA methylation (Reytor et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In total, 34 target genes were identified, among which, S-adenosylmethionine synthetase (SAM) was the only predicted target of the only known differentially expressed miRNA mir-2788. SAM is also known as methionine adenosyltransferase (MAT), catalyzes the formation of S-adenosylmethionine by joining methionine and ATP (Horikawa et al 1990), and plays an important role in plant responses to salt, drought, alkali, and flood stresses (Kamal et al 2012;Chen et al 2014). SAM is also a methyl donor, which controls gene expression by DNA methylation (Reytor et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Protection against high or low temperatures, salt stress or flooding are particularly important for plant survival, and TCTP is regulated under all these conditions. For example, a recent study on maize leaves subjected to flooding stress, reported that TCTP was increased in response to flooding stress, possibly mediated by increased production of hydrogen peroxide (Chen et al 2014b). TCTP from the rubber tree (Hevea brasiliensis) was found to be regulated by drought, low temperature, high salt, ethylene, hydrogen peroxide or wounding (Deng et al 2016;Li et al 2013).…”
Section: Involvement In Cellular Stress Responsesmentioning
confidence: 99%
“…There are also examples of TCTP being transcriptionally regulated in stress conditions: (1) Mild oxidative stress induced by hydrogen peroxide was reported to induce transcription activation of TCTP expression through the vitamin D3 receptor (VDR) in keratinocytes (Rid et al 2010) and plants (maize) under flood stress conditions (Chen et al 2014b). (2) Transcriptional induction of TCTP synthesis by heavy metals has been observed very early in earthworms (Sturzenbaum et al 1998).…”
Section: Transcriptional Regulation Of Tpt1 Gene Expressionmentioning
confidence: 99%
“…It is now generally accepted that lack of oxygen induces synthesis of anaerobic stress proteins belonging to the signal transduction network, to enzymes of the respiratory pathways, carbohydrate mobilization, nitrogen metabolism, cell wall loosening, and antioxidant defence (Vartapetian and Jackson, 1997;Chirkova and Voitsekovskaya, 1999b). Proteomic studies revealed from about 30 to 70 upregulated proteins in different plants under oxygen shortage (Chen et al, 2014;Yin, Sakata, Nanjo, and Komatsu, 2014).…”
Section: Plant Sciencementioning
confidence: 99%